A spatio‐temporal model for the analysis and prediction of fine particulate matter concentration in Beijing. Issue 1 (25th August 2020) - Wan, Yating; Xu, Minya; Huang, Hui; Xi Chen, Song
Abstract: Effective air quality management and forecasting in Beijing is urgently needed as the region suffers from the worst air pollution in any standards. However, the statistical mechanism of the PM2.5 formation with respect to various factors is underexplored in this region and China in general. Through an elaborate application with refinement of a spatio‐temporal model with varying coefficients to the dynamics of PM2.5 around Beijing based on a large dataset, we provide a comprehensive interpretation for the dynamics of PM2.5 concentration with respect to its gaseous precursors, meteorological conditions and geographical variables. Furthermore, we conduct multistep temporal forecasts on a rolling basis for both the PM2.5 concentration and the pollution levels. With the help of the expectation‐maximization algorithm, the proposed models estimated for eight seasons from March 2015 to February 2017 around Beijing provide satisfactory in‐sample fits and generate more accurate out‐of‐sample forecasts, compared with Finazzi and Fassò's original model as well as other alternative models. Valuable insights in tackling the excessive air pollution in Beijing are suggested from the comprehensive application of our model.